Educação ambiental em zoológicos do nordeste paulista para a conservação da onça parda (Puma concolor) : reflexões sobre atividades e estruturas educadoras - Oliveira, Sara Monise de (Universidade Federal de São Carlos, 2015)
Zoos house many specimens of native fauna and have great potential to contribute to Environmental Education for biodiversity conservation. However, some studies have pointed that even when these institutions carry on biodiversity conservation actions, this subject may be presented in their educational activities or exhibitions. To investigate the potential of zoos in Environmental Education for biodiversity, we chose the cougar (Puma concolor) conservation as motivating topic. It was selected for the reason that this specie is important to biodiversity maintenance in São Paulo State and because there are many challenges in education for big predators conservation. The purpose of this study was to identify environmental education for the cougar conservation strategic actions that zoos could be do; to discuss the educational intent on animal’s exhibition in zoos nowadays; and to analyze the cougar grounds for their potential as facilities that educates for the conservation of this specie. Adopting Freire principles, that grounds the critical environmental education and a hermeneutic research approach, this thesis was set up as a collective instrumental qualitative study case. The research had a diagnostic stage involving five zoos from Sao Paulo northeastern, in which the research first purpose was developed, and a further analysis stage performed with three of these institutions to address the other two purposes of this study. To collect information, we mainly use zoos technical and educational teams interviews, exhibition and cougar exhibit observations; and, finely, informative stuff, websites and technical documents analyses focused on enclosures and animals. The main result of diagnostic was that any specific cougar educational activity had been performed. But, the issue was extremely important for these institutions, which reported many cougars rescues, including some that occurred with animals on display. The teams believe that activities such as campaigns between Sao Paulo State zoos could improve the development of educational stuffs and facilities that educates for this specie conservation. From second stage of the research, we highlight there are two purposes regarding to animals display: firstly it’s to provide close contact with animals and secondly it’s to educate people for nature conservation. These purposes are coherent with zoos conservation goals and environmental education actions. Although, on an educational exhibition it is necessary to set up the balance between elements that explore each one of these purposes. In this sense, the analysis of cougar exhibits shows that the enclosures and its labels doesn’t has been focused on biodiversity conservation. Mediation about this topic it has been done mainly by educators. That reveals enclosures weaknesses on role as facilities that educates, but their potential could be expanded with additional information inclusion that contextualizes the cougar in their locality.
Environmental Education at zoos from Sao Paulo northeastern State (Brazil) for cougar (Puma concolor) conservation : thinking about activities and facilities that educates
Keywords: Atividades educativas; Espaços e estruturas educadoras; Análise de exposições; Recintos; Estudo de caso qualitativo; Educational activities; Places and facilities that educates; Exhibition analysis; Enclosures; Qualitative study case; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL